HUBUNGAN GANGGUAN KENYAMANAN FISIK DAN PENYAKIT DENGAN KUALITAS TIDUR IBU HAMIL TRIMESTER III - Mariyam Ulfa Sukorini (Universitas Airlangga, 2017)
The older the stages of pregnancy, it was more likely for pregnant women to experience sleep disorder which usually cause physical discomfort and desease (Prasadja, 2009). Poor sleep disorders can cause complications in pregnancy. This study aims to assess the relationship between physical discomfortand presence of disease with sleep quality of women in third trimester of pregnancy. Dependent variable is sleep quality, while Independent variables were pyshical discomfortand presence of disesas. This study used cross-sectional study design and total sampling technique. A total of 36 respondents gathered from Puskesmas Gading’s pregnant women population. PSQI quetionaire used to assess sleep quality (cronbach’s alpha = 0.83)and physical discomfort quetionaire (cronbach’s alpha = 0.672). Every quetionaire’s validity hasbeen tested with r-count > 0.707. All of the data then processed by cross-tabulation and Pearson test. The result of this study showed that most of the respondents have poor sleep quality (53%). Statistical tests showed poor correlation (r = 0.363) between physical discomfort and sleep quality. Furthermore, poor relationship found in pregnant women with disease (r = 0.334).Keywords: physical discomfort, pregnant woman, sleep quality, disease